(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Controlled dc motors are nonlinear systems, that show a nonlinear action in their operation including, sub- harmonics and chaos when they work outside their design specifications. This nonlinearity forces the motor changing its normal operation to a random-like behaviour; In this paper, the nonlinear dynamics of DC motors are investigated. It is shown that the concept of the Poincaré map approach and the monodromy matrix method can be successfully applied to determine the stability of DC motors